2022
DOI: 10.56742/nchat.v2i2.41
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Paritas dan Umur Ibu Hamil Dengan Kejadian Kekurangan Energi Kronik di Desa Simpang Limbur Wilayah Kerja Puskesmas Simpang Limbur

Abstract: Kekurangan energi kronis (KEK) dan anemia pada ibu hamil akan meningkatkan risiko untuk melahirkan bayi dengan berat badan lahir yang rendah. Penelitian ini bertujuan untuk mengetahui hubungan paritas dan umur ibu hamil dengan kejadian kekurangan energy protein (KEK) di Desa Simpang Limbur Wilayah Kerja Puskesmas Simpang Limbur. Desain penelitian yang digunakan adalah observasional analitik dengan pendekatan cross sectional. Populasi pada penelitian ini yaitu seluruh ibu hamil pada bulan September di Desa Simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Educational status may be partly due to a lack of knowledge about proper nutrition during pregnancy and the importance of maintaining healthy weight. Parity is the number of live births a woman has, and high-grade multipara is a high-risk status in pregnancy (Al Rahmad, 2023;Rosita & Rusmimpong, 2022). Previous research has shown a significant relationship between parity and CED incidence in pregnant women (Humairoh et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Educational status may be partly due to a lack of knowledge about proper nutrition during pregnancy and the importance of maintaining healthy weight. Parity is the number of live births a woman has, and high-grade multipara is a high-risk status in pregnancy (Al Rahmad, 2023;Rosita & Rusmimpong, 2022). Previous research has shown a significant relationship between parity and CED incidence in pregnant women (Humairoh et al, 2023).…”
Section: Introductionmentioning
confidence: 99%